Sistem Informasi Pelayanan Administrasi Terpadu pada Kantor Kecamatan Seberang Ulu Satu Kota Palembang - Murni; Ariati, Nining; Dhamayanti (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
Seberang Ulu Satu District of Palembang City is a government institution whose duties include serving community needs in terms of administrative data, in this case specifically regarding licensing and non-licensing services, public complaints and hearse lending services. Based on the observations results, it is found that the mechanism for submitting and managing administrative documents at the Seberang Ulu Satu District office still had some obstacles, such as difficulties for residents to get information about service administration requirements, the requirement for residents to come directly to the office and queues for residents to submit letters applications for both licensing and non-licensing, complaints and borrowing hearses. To overcome this, the authors will design an integrated administrative service information system for Seberang Ulu Satu District, Palembang City using the waterfall software development method, as well as the UML (Unified Modeling Language) design system model which includes use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The end result is building an integrated administrative service information system at the Seberang Ulu Satu District office, Palembang City, which can help and facilitate the process of Integrated Administrative Services for Seberang Ulu Satu District, Palembang City.